2009
DOI: 10.1203/pdr.0b013e318193edf1
|View full text |Cite
|
Sign up to set email alerts
|

Neonates Born to Mothers With Preeclampsia Exhibit Sex-Specific Alterations in Microvascular Function

Abstract: This study aimed to characterize early neonatal microvascular function after preeclamptic pregnancy with respect to infant sex and in utero growth. Peripheral microvascular blood flow was examined prospectively from 6 to 72 h of age using laser Doppler flowmetry in a cohort of term infants of normotensive women and women with late-onset preeclampsia. For male infants, those born to preeclamptic women had greater microvascular blood flow at 6 h (p Ͻ 0.05) with no change over time. Male infants of normotensive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…Studies of preterm infants born to mothers with pregnancy-induced hypertension treated with antihypertensive medications, including MgSO 4 , have also reported reduced cFTOE in the first 24 h of life (18). The generalization of this latter study to preterm infants of normotensive mothers, however, is limited, given that pregnancy induced hypertension results in alterations in placental blood flow (22), and both fetal and neonatal circulations (23,24). For instance, CBF may be greater in infants with evidence of brain-sparing in pregnancies complicated by pregnancy induced hypertension as a result of changes in fetal cerebral vascular resistance (23).…”
Section: Discussionmentioning
confidence: 81%
“…Studies of preterm infants born to mothers with pregnancy-induced hypertension treated with antihypertensive medications, including MgSO 4 , have also reported reduced cFTOE in the first 24 h of life (18). The generalization of this latter study to preterm infants of normotensive mothers, however, is limited, given that pregnancy induced hypertension results in alterations in placental blood flow (22), and both fetal and neonatal circulations (23,24). For instance, CBF may be greater in infants with evidence of brain-sparing in pregnancies complicated by pregnancy induced hypertension as a result of changes in fetal cerebral vascular resistance (23).…”
Section: Discussionmentioning
confidence: 81%
“…This increase in prosurvival factors might confer further protection against stress conditions, and might play a key role in sex differences in fetal outcomes. It was previously shown that under similar conditions, female fetuses make multiple adaptations in placental gene and protein expression in response to intrauterine adversity, such as maternal asthma, preeclampsia 44,45 and maternal stress, 46 while male fetuses show fewer signs of adaptation. 47 Our study, however, revealed that male fetuses did respond to maternal obesity with placental autophagy though with a disrupted autophagic flux as indicated by inhibited autolysosomal protein degradation and lysosomal biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The following variables were collected from hospital records: sex, 16,17 gestational age, 18 maternal hypertension during pregnancy, 17 gestational diabetes, 19 and mode of delivery. 20 Assisted pregnancy and parity were also considered potentially important, as was blood pressure of the infant.…”
Section: Covariatesmentioning
confidence: 99%